A kind of high-strength inorganic thin spraying reinforcement material for mining and preparation method thereof
By using high-strength mineral inorganic thin-blown reinforcement materials for mining in the underground tunnels, high-strength, hydrophobic, corrosion-resistant and high flame-retardant inorganic thin-blown reinforcement materials are blended, which solves the problems of complex construction, high cost and limited support strength in the existing technology, and achieves an efficient and environmentally friendly tunnel reinforcement effect.
Patent Information
- Application Number
- CN202411526490.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The prior art has problems such as complex construction technology, high cost, poor dust environment and limited support strength in terms of sealing, reinforcement, waterproofing and corrosion resistance of underground tunnels.
High-strength inorganic thin-blown reinforcement materials for mining are used to blend adhesives, environmentally friendly gelling materials, kaolin, toughener and additives, and the components and processes are optimized to prepare high-strength, hydrophobic, corrosion-resistant, and high flame-retardant inorganic thin-blown reinforcement materials.
It achieves high strength, hydrophobic, corrosion-resistant and high flame retardant effects, reduces the use of cement, reduces the risk of environmental pollution, and extends the service life of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of reinforcement materials, in particular to a high-strength inorganic thin-spray reinforcement material for mining and a preparation method thereof. Background Art
[0002] As the scale of mining expands, the environmental and geological conditions faced are becoming increasingly complex. The sealing, reinforcement, waterproofing, and corrosion resistance of underground tunnels are closely related to mine production safety.
[0003] In order to solve the problems of weathering of surrounding rocks and rusting of anchor metal mesh, sprayed mortar or concrete is currently used to seal the tunnels, but there are also the following problems, such as complex construction process, high cost, poor dust environment at the construction site, and limited support strength for the tunnels. Therefore, it is of practical significance and economic value to develop a high-strength inorganic thin spray reinforcement material for mining, which is suitable for the sealing, reinforcement, waterproofing and corrosion resistance of underground tunnels. Summary of the invention
[0004] The purpose of the present invention is to provide a high-strength inorganic thin-spray reinforcement material for mining and a preparation method thereof, so as to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A high-strength inorganic thin-spray reinforcement material for mining, which comprises the following raw materials, measured in parts by weight: 22-33 parts of adhesive, 27-37 parts of environmentally friendly cementitious material, 5-12 parts of kaolin, 3-6 parts of toughening agent, and 6-12 parts of auxiliary agent; the toughening agent is composed of redispersible latex powder and modified basalt fiber in a weight ratio of 1:1.
[0007] Furthermore, the auxiliary agent is a water reducing agent, a film-forming agent, and a defoaming agent compounded in a mass ratio of 1:3:1.
[0008] Furthermore, the adhesive is one or a combination of acrylamide, polyvinyl alcohol, and hydroxypropyl starch ether.
[0009] Furthermore, the environmentally friendly cementitious material is obtained by compounding waste foam concrete, steel slag, slag and sulphoaluminate cement in a mass ratio of 4:3:6:5.
[0010] Furthermore, the preparation of the environmentally friendly cementitious material includes the following steps: crushing, screening and pulverizing the waste foam concrete, steel slag and slag in turn, adding sulphoaluminate cement, mixing and stirring, grinding and sieving, and washing with sodium sulfate solution for 5-8 times to obtain the environmentally friendly cementitious material.
[0011] Furthermore, the adhesive is obtained by compounding polyvinyl alcohol and modified acrylamide in a mass ratio of 1:2.
[0012] Further, the preparation of modified acrylamide comprises the following steps:
[0013] Under a nitrogen atmosphere, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, acrylamide, and deionized water are mixed, N-dodecyl acrylamide, a bio-based flame retardant, sodium dodecyl sulfate, and 2,2-dimethoxy-2-phenylacetophenone are added, and 365 nm ultraviolet light is used for 3-4 hours to obtain modified acrylamide.
[0014] Further, the preparation of modified basalt fiber includes the following steps:
[0015] (1) Mix basalt fiber and sodium bisulfate monohydrate, add N,N-dimethylformamide and thioglycolic acid, heat to 118-122°C and keep warm for 3-4 hours, add sodium sulfide nonahydrate and anhydrous ethanol, stir for 1-2 hours, wash with deionized water, dry, grind, and sieve to obtain thiolated basalt fiber;
[0016] (2) Under a nitrogen atmosphere, thiolated basalt fiber and ethyl acetate are mixed, a bio-based flame retardant and 2,2-dimethoxy-2-phenylacetophenone are added, the temperature is raised to 60-70°C, and ultraviolet light with a wavelength of 365 nm is irradiated for 1-2 hours to obtain modified basalt fiber.
[0017] Furthermore, the preparation of the bio-based flame retardant comprises the following steps:
[0018] 1) Mix eugenol and ethyl acetate, add a mixture of triethylamine and ethyl acetate, cool in an ice bath at 0°C for 8-10 minutes, add phenyl dichlorophosphate and ethyl acetate in sequence, keep warm at 18-25°C for 22-24 hours, separate, wash, and rotary evaporate to obtain a double-bond-terminated eugenol-based flame retardant;
[0019] 2) Mix dibenzothiazole disulfide and chloroform, add β-mercaptoethanol, stir at 18-25°C for 5-8h, concentrate, filter, wash with deionized water 3-5 times, and dry to obtain an intermediate preparation;
[0020] 3) Under a nitrogen atmosphere, the intermediate preparation and ethyl acetate are mixed, a double-bond-terminated eugenol-based flame retardant and 2,2-dimethoxy-2-phenylacetophenone are added, the temperature is raised to 58-62° C., and ultraviolet light with a wavelength of 365 nm is irradiated for 1-2 hours to obtain a bio-based flame retardant.
[0021] Furthermore, a method for preparing a high-strength inorganic thin-sprayed reinforcement material for mining includes the following steps: mixing an adhesive, an environmentally friendly cementitious material, kaolin, a toughening agent, and an additive, and ultrasonically stirring to obtain a high-strength inorganic thin-sprayed reinforcement material for mining.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The invention provides a high-strength inorganic thin-sprayed reinforcement material for mining and a preparation method thereof. By optimizing components and processes, a high-strength, hydrophobic, corrosion-resistant and highly flame-retardant inorganic thin-sprayed reinforcement material for mining is prepared.
[0024] In the present invention, inorganic thin-spray reinforcement materials are prepared by blending adhesives, environmentally friendly cementitious materials, kaolin, toughening agents, and additives. Adhering to the concept of green development, the present invention selects waste foam concrete, steel slag, slag, and sulphoaluminate cement to prepare environmentally friendly cementitious materials. Through the ratio of ingredients, the addition of industrial solid waste reduces the use of cement, thereby reducing the risk of environmental pollution and achieving the effect of saving production costs.
[0025] In order to improve the toughness of inorganic thin spray reinforcement materials, redispersible latex powder is selected and compounded with basalt fiber with high strength, high modulus, good temperature resistance, good filterability and strong applicability. In order to improve the uniformity of basalt fiber dispersion in the material, the basalt fiber is modified, and thioglycolic acid is used to introduce thiol groups. Then, through the thiol-double bond photo-click reaction, a bio-based flame retardant containing a double bond at one end and an antifouling group at the other end is grafted, thereby greatly improving the antifouling, corrosion resistance and flame retardancy of inorganic thin spray reinforcement materials.
[0026] The bio-based flame retardant is a double-bond-terminated eugenol-based flame retardant prepared by reacting the bio-based raw material eugenol with phenyl dichloride phosphate, and then dibenzothiazole disulfide and β-mercaptoethanol are used as raw materials to prepare an intermediate preparation with anti-fouling and corrosion inhibition properties by utilizing a disulfide-thiol exchange reaction. By controlling the raw material ratio of the intermediate preparation and the double-bond-terminated eugenol-based flame retardant, a photoclick reaction is caused to occur to generate a bio-based flame retardant having a double bond at one end and an anti-fouling group at the other end.
[0027] In order to improve the adhesion of inorganic thin spray reinforcement materials, polyvinyl alcohol and acrylamide are selected as adhesives. In order to give the inorganic thin spray reinforcement materials excellent waterproofness, high temperature resistance and salt resistance, acrylamide is modified and prepared by photoinitiated micelle polymerization with acrylic acid, 2-acrylamide-2-methylpropane sulfonic acid, acrylamide, N-dodecyl acrylamide and bio-based flame retardant as raw materials. The bonding strength between the inorganic thin spray reinforcement materials and the substrate is improved, so that the inorganic thin spray reinforcement materials are firmly attached to the surface of the substrate, and excellent hydrophobicity, flame retardancy, thermal stability and corrosion resistance are given to the inorganic thin spray reinforcement materials, thereby extending the service life of the inorganic thin spray reinforcement materials. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0030] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0031] Embodiment 1: A method for preparing a high-strength inorganic thin-spray reinforcement material for mining, comprising the following steps: mixing an adhesive, an environmentally friendly cementitious material, kaolin, a toughening agent, and an additive, and ultrasonically stirring to obtain a high-strength inorganic thin-spray reinforcement material for mining;
[0032] In parts by weight, the raw materials of the reinforcement material are composed of: 22 parts of adhesive, 27 parts of environmentally friendly gelling material, 5 parts of kaolin, 3 parts of toughening agent, and 6 parts of auxiliary agent; the toughening agent is composed of redispersible latex powder and modified basalt fiber in a weight ratio of 1:1;
[0033] The auxiliary agent is a compound of a water reducing agent, a film-forming agent and a defoaming agent in a mass ratio of 1:3:1;
[0034] The environmentally friendly cementitious material is obtained by compounding waste foam concrete, steel slag, slag and sulphoaluminate cement in a mass ratio of 4:3:6:5;
[0035] The preparation of the environmentally friendly cementitious material comprises the following steps: crushing, screening and pulverizing the waste foam concrete, steel slag and slag in sequence, adding sulphoaluminate cement, mixing and stirring, grinding, passing through a 200-mesh sieve, and washing five times with a sodium sulfate solution with a mass concentration of 12% to obtain the environmentally friendly cementitious material;
[0036] The adhesive is prepared by compounding polyvinyl alcohol and modified acrylamide in a mass ratio of 1:2; the preparation of the modified acrylamide comprises the following steps:
[0037] Under nitrogen atmosphere, 12 g acrylic acid, 1 g 2-acrylamide-2-methylpropanesulfonic acid, 26 g acrylamide, and 100 mL deionized water were mixed, 4 g N-dodecyl acrylamide, 5 g bio-based flame retardant, 1.5 g sodium dodecyl sulfate, and 0.4 g 2,2-dimethoxy-2-phenylacetophenone were added, and irradiated with 365 nm ultraviolet light for 3 h to obtain modified acrylamide;
[0038] The preparation of the modified basalt fiber comprises the following steps:
[0039] (1) 10 g of basalt fiber and 0.25 g of sodium bisulfate monohydrate were mixed, 25 mL of N,N-dimethylformamide and 50 mL of thioglycolic acid were added, the temperature was raised to 118 °C and kept for 4 h, 60 g of sodium sulfide nonahydrate and 125 mL of anhydrous ethanol were added, the mixture was stirred for 1 h, the mixture was washed with deionized water, dried, ground, and sieved to obtain thiolated basalt fiber;
[0040] (2) Under a nitrogen atmosphere, 3.2 g of thiolated basalt fiber and 45 mL of ethyl acetate were mixed, 7.8 g of a bio-based flame retardant and 0.8 g of 2,2-dimethoxy-2-phenylacetophenone were added, the temperature was raised to 60 ° C, and ultraviolet light with a wavelength of 365 nm was used for 1 h to obtain modified basalt fiber;
[0041] The preparation of the bio-based flame retardant comprises the following steps:
[0042] 1) 2 g of eugenol and 9 mL of ethyl acetate were mixed, and a mixture of 1.2 g of triethylamine and 9 mL of ethyl acetate was added, and the mixture was cooled in an ice bath at 0°C for 8 min, and 1.3 g of phenyl dichlorophosphate and 2 mL of ethyl acetate were added in sequence, and the mixture was kept warm at 18°C for 24 h, and the mixture was separated, washed, and rotary evaporated to obtain a double-bond-terminated eugenol-based flame retardant;
[0043] 2) Mix 3.3 g of dibenzothiazole disulfide and 45 mL of chloroform, add 3.1 g of β-mercaptoethanol, stir at 18 °C for 8 h, concentrate, filter, wash with deionized water three times, and dry to obtain an intermediate preparation;
[0044] 3) Under a nitrogen atmosphere, 2 g of the intermediate preparation and 40 mL of ethyl acetate were mixed, 6 g of a double-bond-terminated eugenol-based flame retardant and 0.2 g of 2,2-dimethoxy-2-phenylacetophenone were added, the temperature was raised to 58°C, and ultraviolet light with a wavelength of 365 nm was used for irradiation for 1 h to obtain a bio-based flame retardant.
[0045] Embodiment 2: A method for preparing a high-strength inorganic thin-sprayed reinforcement material for mining, comprising the following steps: mixing an adhesive, an environmentally friendly gelling material, kaolin, a toughening agent, and an additive, and ultrasonically stirring to obtain a high-strength inorganic thin-sprayed reinforcement material for mining;
[0046] In parts by weight, the raw materials of the reinforcement material are composed of: 26 parts of adhesive, 33 parts of environmentally friendly gelling material, 7 parts of kaolin, 4 parts of toughening agent, and 8 parts of auxiliary agent; the toughening agent is composed of redispersible latex powder and modified basalt fiber in a weight ratio of 1:1;
[0047] The auxiliary agent is a compound of a water reducing agent, a film-forming agent and a defoaming agent in a mass ratio of 1:3:1;
[0048] The environmentally friendly cementitious material is obtained by compounding waste foam concrete, steel slag, slag and sulphoaluminate cement in a mass ratio of 4:3:6:5;
[0049] The preparation of the environmentally friendly cementitious material comprises the following steps: crushing, screening and pulverizing the waste foam concrete, steel slag and slag in sequence, adding sulphoaluminate cement, mixing and stirring, grinding, passing through a 200-mesh sieve, and washing with a sodium sulfate solution with a mass concentration of 12% for 6 times to obtain the environmentally friendly cementitious material;
[0050] The adhesive is prepared by compounding polyvinyl alcohol and modified acrylamide in a mass ratio of 1:2; the preparation of the modified acrylamide comprises the following steps:
[0051] Under nitrogen atmosphere, 12 g acrylic acid, 1 g 2-acrylamide-2-methylpropanesulfonic acid, 26 g acrylamide, and 100 mL deionized water were mixed, 4 g N-dodecyl acrylamide, 5 g bio-based flame retardant, 1.5 g sodium dodecyl sulfate, and 0.4 g 2,2-dimethoxy-2-phenylacetophenone were added, and irradiated with 365 nm ultraviolet light for 3.5 h to obtain modified acrylamide;
[0052] The preparation of the modified basalt fiber comprises the following steps:
[0053] (1) 10 g of basalt fiber and 0.25 g of sodium bisulfate monohydrate were mixed, 25 mL of N,N-dimethylformamide and 50 mL of thioglycolic acid were added, the temperature was raised to 120 °C and kept for 3.5 h, 60 g of sodium sulfide nonahydrate and 125 mL of anhydrous ethanol were added, and the mixture was stirred for 1.5 h. The mixture was washed with deionized water, dried, ground, and sieved to obtain thiolated basalt fiber;
[0054] (2) Under a nitrogen atmosphere, 3.2 g of thiolated basalt fiber and 45 mL of ethyl acetate were mixed, 7.8 g of a bio-based flame retardant and 0.8 g of 2,2-dimethoxy-2-phenylacetophenone were added, the temperature was raised to 65 ° C, and ultraviolet light with a wavelength of 365 nm was used for 1.5 h to obtain modified basalt fiber;
[0055] The preparation of the bio-based flame retardant comprises the following steps:
[0056] 1) 2 g of eugenol and 9 mL of ethyl acetate were mixed, and a mixture of 1.2 g of triethylamine and 9 mL of ethyl acetate was added, and the mixture was cooled in an ice bath at 0°C for 9 min, and 1.3 g of phenyl dichlorophosphate and 2 mL of ethyl acetate were added in sequence, and the mixture was kept warm at 20°C for 23 h, and the mixture was separated, washed, and rotary evaporated to obtain a double-bond-terminated eugenol-based flame retardant;
[0057] 2) Mix 3.3 g of dibenzothiazole disulfide and 45 mL of chloroform, add 3.1 g of β-mercaptoethanol, stir at 20 °C for 6 h, concentrate, filter, wash with deionized water 4 times, and dry to obtain an intermediate preparation;
[0058] 3) Under a nitrogen atmosphere, 2 g of the intermediate preparation and 40 mL of ethyl acetate were mixed, 6 g of a double-bond-terminated eugenol-based flame retardant and 0.2 g of 2,2-dimethoxy-2-phenylacetophenone were added, the temperature was raised to 60°C, and ultraviolet light with a wavelength of 365 nm was used for irradiation for 1.5 h to obtain a bio-based flame retardant.
[0059] Embodiment 3: A method for preparing a high-strength inorganic thin-sprayed reinforcement material for mining, comprising the following steps: mixing an adhesive, an environmentally friendly gelling material, kaolin, a toughening agent, and an additive, and ultrasonically stirring to obtain a high-strength inorganic thin-sprayed reinforcement material for mining;
[0060] In parts by weight, the raw materials of the reinforcement material are composed of: 33 parts of adhesive, 37 parts of environmentally friendly gelling material, 12 parts of kaolin, 6 parts of toughening agent, and 12 parts of auxiliary agent; the toughening agent is composed of redispersible latex powder and modified basalt fiber in a weight ratio of 1:1;
[0061] The auxiliary agent is a compound of a water reducing agent, a film-forming agent and a defoaming agent in a mass ratio of 1:3:1;
[0062] The environmentally friendly cementitious material is obtained by compounding waste foam concrete, steel slag, slag and sulphoaluminate cement in a mass ratio of 4:3:6:5;
[0063] The preparation of the environmentally friendly cementitious material comprises the following steps: crushing, screening and pulverizing the waste foam concrete, steel slag and slag in sequence, adding sulphoaluminate cement, mixing and stirring, grinding, passing through a 200-mesh sieve, and washing 8 times with a sodium sulfate solution with a mass concentration of 12% to obtain the environmentally friendly cementitious material;
[0064] The adhesive is prepared by compounding polyvinyl alcohol and modified acrylamide in a mass ratio of 1:2; the preparation of the modified acrylamide comprises the following steps:
[0065] Under nitrogen atmosphere, 12 g acrylic acid, 1 g 2-acrylamide-2-methylpropanesulfonic acid, 26 g acrylamide, and 100 mL deionized water were mixed, 4 g N-dodecyl acrylamide, 5 g bio-based flame retardant, 1.5 g sodium dodecyl sulfate, and 0.4 g 2,2-dimethoxy-2-phenylacetophenone were added, and irradiated with 365 nm ultraviolet light for 4 h to obtain modified acrylamide;
[0066] The preparation of the modified basalt fiber comprises the following steps:
[0067] (1) 10 g of basalt fiber and 0.25 g of sodium bisulfate monohydrate were mixed, 25 mL of N,N-dimethylformamide and 50 mL of thioglycolic acid were added, the temperature was raised to 122 °C and kept for 3 h, 60 g of sodium sulfide nonahydrate and 125 mL of anhydrous ethanol were added, and the mixture was stirred for 2 h. The mixture was washed with deionized water, dried, ground, and sieved to obtain thiolated basalt fiber;
[0068] (2) Under a nitrogen atmosphere, 3.2 g of thiolated basalt fiber and 45 mL of ethyl acetate were mixed, 7.8 g of a bio-based flame retardant and 0.8 g of 2,2-dimethoxy-2-phenylacetophenone were added, the temperature was raised to 70 ° C, and ultraviolet light with a wavelength of 365 nm was used for 2 h to obtain modified basalt fiber;
[0069] The preparation of the bio-based flame retardant comprises the following steps:
[0070] 1) Mix 2 g of eugenol and 9 mL of ethyl acetate, add a mixture of 1.2 g of triethylamine and 9 mL of ethyl acetate, cool in an ice bath at 0°C for 10 min, add 1.3 g of phenyl dichlorophosphate and 2 mL of ethyl acetate in sequence, keep warm at 25°C for 22 h, separate, wash, and rotary evaporate to obtain a double-bond-terminated eugenol-based flame retardant;
[0071] 2) Mix 3.3 g of dibenzothiazole disulfide and 45 mL of chloroform, add 3.1 g of β-mercaptoethanol, stir at 25 °C for 5 h, concentrate, filter, wash with deionized water 5 times, and dry to obtain an intermediate preparation;
[0072] 3) Under a nitrogen atmosphere, 2 g of the intermediate preparation and 40 mL of ethyl acetate were mixed, 6 g of a double-bond-terminated eugenol-based flame retardant and 0.2 g of 2,2-dimethoxy-2-phenylacetophenone were added, the temperature was raised to 62°C, and ultraviolet light with a wavelength of 365 nm was used for irradiation for 2 h to obtain a bio-based flame retardant.
[0073] Comparative Example 1: Taking Example 3 as the control group, basalt fiber was used to replace the modified basalt fiber, and other processes were normal.
[0074] Comparative Example 2: Taking Example 3 as the control group, acrylamide was used to replace the modified acrylamide, and the other processes were normal.
[0075] Comparative Example 3: Example 3 was used as the control group, no bio-based flame retardant was prepared, and other processes were normal.
[0076] Sources of raw materials used (for demonstration purposes only):
[0077] Kaolin (99%): Tai'an Jiangzhou Biotechnology Co., Ltd.; redispersible latex powder YLD-04-01: Shandong Yonglida New Material Technology Co., Ltd.; water reducer A00352, sulphoaluminate cement A00305: Wuhan Jiyesheng Chemical Co., Ltd.; film former DPNB: Guangzhou Hengyu Chemical Co., Ltd.; defoamer (polyether L61): Linyi Guoli Chemical Co., Ltd.; waste foam concrete (density 600kg / m 3 , thermal conductivity of 0.15W / (m·k), 28d strength of 5MPa, commercially available); steel slag JS10-10, slag GSB08-1534-2014: Henan Detong Environmental Protection Technology Co., Ltd.; basalt fiber (diameter 20µm): Guangdong Zhongtian Port Bridge Construction Engineering Co., Ltd.; 2,2-dimethoxy-2-phenylacetophenone S45044: Shanghai Yuanye Biotechnology Co., Ltd.; 2-acrylamide-2-methylpropanesulfonic acid (98%): Shandong Yonglida New Materials Technology Co., Ltd.; thioglycolic acid 68-11-1: Shandong Jinyueyuan New Materials Co., Ltd.; polyvinyl alcohol P13 9546, acrylic acid A103526, acrylamide A108465, N-dodecyl acrylamide N159038, sodium dodecyl sulfate S432157, sodium hydrogen sulfate monohydrate S108850, N,N-dimethylformamide D111999, sodium sulfide nonahydrate S299093, eugenol E110640, triethylamine T103285, phenyl dichloride phosphate P104277, dibenzothiazyl disulfide D110137, β-mercaptoethanol M301573: Aladdin reagent; sodium sulfate, anhydrous ethanol, ethyl acetate, chloroform, analytical grade: Sinopharm reagent.
[0078] Performance test: The inorganic thin spray reinforcement materials prepared in the embodiments and comparative examples were tested:
[0079] The inorganic thin spray reinforcement material was mixed with water at a water-cement ratio of 0.4, and then injected into a 40mm×40mm×160mm mold, covered with plastic wrap, and demoulded after curing in a standard curing room for 24 hours to obtain a sample;
[0080] Compressive strength: the sample was subjected to standard curing for 28 days, and then subjected to strength test, and the compressive strength test was conducted in accordance with GB / T17671-2021; Hydrophobicity: the water contact angle was tested using a contact angle meter, with a 4μL deionized water droplet; Flame retardancy: the UL-94 vertical combustion flame retardant grade test was conducted; Corrosion resistance: the sample was kept at 200°C for 2 hours, cooled, and then immersed in a 10% sodium chloride solution for 48 hours, and the compressive strength was measured again and compared with the initial compressive strength. When the change rate of the compressive strength was between 0% and 2% (including 2%), it was qualified, otherwise it was unqualified; the results are shown in Table 1;
[0081] Table 1
[0082]
[0083] The invention provides a high-strength inorganic thin-sprayed reinforcement material for mining and a preparation method thereof. By optimizing components and processes, a high-strength, hydrophobic, corrosion-resistant and highly flame-retardant inorganic thin-sprayed reinforcement material for mining is prepared.
[0084] By comparing Example 3 with Comparative Example 1 and Comparative Example 3, it can be seen that in order to improve the toughness of the inorganic thin spray reinforcement material, a redispersible latex powder is selected and compounded with a basalt fiber with high strength, high modulus, good temperature resistance, good filterability and strong applicability. In order to improve the uniformity of the dispersion of the basalt fiber in the material, the basalt fiber is modified, and a thiol group is introduced by using thioglycolic acid, and then a bio-based flame retardant containing a double bond at one end and an antifouling group at the other end is grafted through a thiol-double bond photoclick reaction, thereby greatly improving the antifouling, corrosion resistance and flame retardancy of the inorganic thin spray reinforcement material;
[0085] The bio-based flame retardant is a double-bond-terminated eugenol-based flame retardant prepared by reacting the bio-based raw material eugenol with phenyl dichloride phosphate, and then dibenzothiazole disulfide and β-mercaptoethanol are used as raw materials to prepare an intermediate preparation with anti-fouling and corrosion inhibition properties by utilizing a disulfide-thiol exchange reaction. By controlling the raw material ratio of the intermediate preparation and the double-bond-terminated eugenol-based flame retardant, a photoclick reaction is caused to occur to generate a bio-based flame retardant having a double bond at one end and an anti-fouling group at the other end.
[0086] By comparing Example 3 with Comparative Examples 2 and 3, it can be seen that in order to improve the adhesion of the inorganic thin spray reinforcement material, polyvinyl alcohol and acrylamide are selected as the adhesive. In order to give the inorganic thin spray reinforcement material excellent waterproofness, high temperature resistance and salt resistance, acrylamide is modified and prepared by light-initiated micelle polymerization using acrylic acid, 2-acrylamide-2-methylpropane sulfonic acid, acrylamide, N-dodecyl acrylamide and bio-based flame retardant as raw materials. The bonding strength between the inorganic thin spray reinforcement material and the substrate is improved, so that the inorganic thin spray reinforcement material is firmly attached to the surface of the substrate, and excellent hydrophobicity, flame retardancy, thermal stability and corrosion resistance are given to the inorganic thin spray reinforcement material, thereby extending the service life of the inorganic thin spray reinforcement material.
[0087] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A high-strength inorganic thin spray reinforcement material for mining, characterized in that: In parts by weight, the raw materials of the reinforcement material are composed of: 22-33 parts of adhesive, 27-37 parts of environmentally friendly gelling material, 5-12 parts of kaolin, 3-6 parts of toughening agent, and 6-12 parts of auxiliary agent; The toughening agent is composed of redispersible latex powder and modified basalt fiber in a weight ratio of 1:1; The adhesive is prepared by compounding polyvinyl alcohol and modified acrylamide in a mass ratio of 1:2; The preparation of the modified acrylamide comprises the following steps: Under a nitrogen atmosphere, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, acrylamide, and deionized water are mixed, N-dodecyl acrylamide, a bio-based flame retardant, sodium dodecyl sulfate, and 2,2-dimethoxy-2-phenylacetophenone are added, and irradiated with 365 nm ultraviolet light for 3-4 hours to obtain modified acrylamide; The preparation of the modified basalt fiber comprises the following steps: (1) Mix basalt fiber and sodium bisulfate monohydrate, add N,N-dimethylformamide and thioglycolic acid, heat to 118-122°C and keep warm for 3-4 hours, add sodium sulfide nonahydrate and anhydrous ethanol, stir for 1-2 hours, wash with deionized water, dry, grind, and sieve to obtain thiolated basalt fiber; (2) Under a nitrogen atmosphere, thiolated basalt fiber and ethyl acetate are mixed, a bio-based flame retardant and 2,2-dimethoxy-2-phenylacetophenone are added, the temperature is raised to 60-70° C., and ultraviolet light with a wavelength of 365 nm is irradiated for 1-2 hours to obtain modified basalt fiber; The preparation of the bio-based flame retardant comprises the following steps: 1) Mix eugenol and ethyl acetate, add a mixture of triethylamine and ethyl acetate, cool in an ice bath at 0°C for 8-10 minutes, add phenyl dichlorophosphate and ethyl acetate in sequence, keep warm at 18-25°C for 22-24 hours, separate, wash, and rotary evaporate to obtain a double-bond-terminated eugenol-based flame retardant; 2) Mix dibenzothiazole disulfide and chloroform, add β-mercaptoethanol, stir at 18-25°C for 5-8h, concentrate, filter, wash with deionized water 3-5 times, and dry to obtain an intermediate preparation; 3) Under a nitrogen atmosphere, the intermediate preparation and ethyl acetate are mixed, a double-bond-terminated eugenol-based flame retardant and 2,2-dimethoxy-2-phenylacetophenone are added, the temperature is raised to 58-62° C., and ultraviolet light with a wavelength of 365 nm is irradiated for 1-2 hours to obtain a bio-based flame retardant.
2. The high-strength inorganic thin spray reinforcement material for mining according to claim 1 is characterized in that: The auxiliary agent is a water reducing agent, a film-forming agent and a defoaming agent, which are compounded in a mass ratio of 1:3:
1.
3. The high-strength inorganic thin spray reinforcement material for mining according to claim 1 is characterized in that: The adhesive is one or a combination of acrylamide, polyvinyl alcohol and hydroxypropyl starch ether.
4. The high-strength inorganic thin spray reinforcement material for mining according to claim 1, characterized in that: The environmentally friendly cementitious material is obtained by compounding waste foam concrete, steel slag, slag and sulphoaluminate cement in a mass ratio of 4:3:6:
5.
5. The high-strength inorganic thin spray reinforcement material for mining according to claim 1, characterized in that: The preparation of the environmentally friendly cementitious material comprises the following steps: crushing, screening and pulverizing the waste foam concrete, steel slag and slag in sequence, adding sulphoaluminate cement, mixing and stirring, grinding and sieving, and washing with sodium sulfate solution for 5-8 times to obtain the environmentally friendly cementitious material.
6. A method for preparing a high-strength inorganic thin spray reinforcement material for mining according to any one of claims 1 to 5, characterized in that: The following steps are involved: Adhesive, environmentally friendly cementitious material, kaolin, toughening agent and additive are mixed and ultrasonically stirred to obtain a high-strength inorganic thin-spray reinforcement material for mining.
Citation Information
Patent Citations
Flame-retardant air-leakage-proof static non-reaction environment-friendly sealing and reinforcing composite thin spraying material
CN115557762A
Basalt fiber sprayed concrete and preparation method thereof
CN118271052A